ALAT PENGONTROL PERANGKAT ELEKTRONIK BERBASIS IOT MENGGUNAKAN BLYNK DAN GOOGLE ASSISTANT - Azril Mulyana; Sri Rahmawati; Robby Rahman; Zulia Nur Permatasari (LPPM Universitas Widya Dharma, 2022)
Rapid technological developments have an impact on the world of industry and society. In everyday life, we are familiar with a device or equipment whose workings are controlled automatically, either semi-automatically or fully automatically. In this era of industry 4.0, there are many electronic devices that function automatically using computer systems. Onei of them is the use ofi technology for thei development ofi smart homes (smarthomes). With this innovation, the operation and use of electrical devices will be very easy, so that human work will be helped. The usei of Internet of Thingsi (IoT) technology on an electronic device, allows these devices to communicate with each other, send and receive data via an Internet pconnection. The purposei of this study is to controli electronic equipment, such asr lights and fans, so thati homeowners cani control these devices remotelyi. The stages carried out in the research are first, the stage of determining Software and Hardware, system design, and the last stage is testing and discussion. In this study, a microcontroller is needed, namely NodeMcu, which functions to control electrical devices, process data, send and receive data to the Blynk server. The way this system works is by issuing commands or conditions from the Google Assistant application and the Blynk application which are connected to the NodeMCU ESP8266 standalone microcontroller to run and control SmartHome devices to reduce power wasted when users forget to turn off Smart Home on Android devices